Digital Promotion Media for the Ornamental Plants Trader During Covid-19 Pandemic - Wardah; Rosmawaty Hilderiah Pandjaitan (LPPM Stikosa - AWS, 2023)
The current uncontrolled Covid-19 pandemic has become a big problem, causing many retail outlets to go bankrupt, unlike the growing ornamental plant business in Indonesia, because more and more people are starting to collect ornamental plants. Caring for ornamental plants is a new trend for activities at home during the Covid-19 pandemic. Homeland business people are starting to realize the importance of implementing digital transformation in trade in the midst of this pandemic, because all activities are carried out from home.The theory used in this research is John December's Computer Mediated Communication (CMC) Theory and Pierre Levy's New Media Theory. CMC is a process of human communication through computers that involves an audience in a certain context, and uses the media for a specific purpose. Pierre Lévy argues that new media is a theory that discusses the development of media. Pierre Levy sees the World Wide Web (www) as an open information environment. Flexible and dynamic, enabling people to develop new knowledge orientations. This research method is qualitative research. The paradigm used in this research is constructivist. The data for this study were collected by interviewing informants. The results of this study indicate that ornamental plant traders on Jalan Menara Anteve Kavling DKI, West Jakarta, use digital media to promote their ornamental plants. WhatsApp, Facebook, Instagram, YouTube, Shopee, Tokopedia, and personal blogs are platforms used by ornamental plant traders to promote their ornamental plants at the ornamental plant sales center on Jalan Menara Anteve Kavling DKI West Jakarta. When conducting digital promotions, merchants use smartphones exclusively. This means that the ornamental plant traders on Jalan Menara Anteve Kavling DKI West Jakarta are less creative and have not maximally used various computerized communication facilities.